HAK DAN AKTIVITAS POLITIK WANITA PERSPEKTIF ABŪ AL-A‘LĀ AL-MAUDŪDĪ - Putri Adelia (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2019)
There is an assumption that develops in society that according to religion women have no place in social life and women's role is limited only in the domestic sphere. The implication is that women are not allowed to take roles in the public sphere, such as being educated as equals to men, working outside the home, even taking part in political territory. One of the modern-day Muslim scholars who interpreted the verse as a limitation on women leaving the house was Abū al-A‘lā al-Maudūdī. The author is interested in further examining his interpretation because it is classified into modern commentators but some interpretations related to women seem to be gender biased. This paper will discuss al-Maudūdī's interpretation of the QS. Al-Aḥzāb: 33 this verse is said to be the initial foothold regarding perceptions of restrictions on the movement of women in the public sphere resulting from an understanding of the results of the interpretation of orders for women to always remain at home. Then examine how this interpretation affects women's political activities.